Cost-effectveness of integrated pest management compared with insecticidal spraying against the German cockroach in apartment buildings. - Shahraki, Gholam Hossein; Mohd Noor, Hafidzi; Shahar, Mohd Khadri; Rafinejad, Javad; Ibrahim, Yusof (Entomological Society of Brazil, 2011)
This study assessed the cost and effectiveness of an integrated pest management (IPM) program using hydramethylnon gel baits compared with conventional spraying for controlling the German cockroach, Blattella germanica (L.) (Blattodea: Blattellidae), in two residential buildings in Yasuj, Iran. The IPM approach was based on educational programs using pamphlets, posters and lectures, sanitation using vacuuming and application of hydramethylnon gel baits. Conventional approach used cypermethrin (10% EC) on baseboard and cracks-and-crevices. Sticky traps were used as tools for monitoring cockroach population densities. The IPM approach reduced (943%) the rate of insecticide application compared to the conventional spray. Cockroach populations in the IPM treatment were significantly reduced from an average of 12.2 ± 3.01 cockroaches per unit before treatment to zero cockroach per unit by week four and thereafter. Cockroach populations in the conventional spray treatment were reduced from an average of 11.5 ± 4.43 cockroaches per unit before treatment to an average of 3.4 ± 0.99 cockroach per unit after 11 weeks of post treatment. The IPM treatment improved 100% of infested units compared to 78% for spray treatment to obtain a clean level of infestation (< 1cockroach per trap per unit). The results suggest that the intervention by IPM using hydramethylnon gel baits significantly reduced cockroach infestation compared to cypermethrin spray throughout the 11 weeks of post-treatment period. However, within the study period, the IPM system involving gel baits, educational program and sanitation was 363.2% more expensive than the conventional method.